PENGUJIAN AKTIVITAS SIRUP EKSTRAK BIJI DAN KULIT BUAH PEPAYA (Carica papaya L.) TERHADAP PERTUMBUHAN Escherichia coli - Djajanti, Agust Dwi Djajanti; Putri Naila (Jurnal Kesehatan Yamasi Makassar, 2025)
This study aims to determine the antibacterial activity and the inhibition zone category of papaya (Carica papaya L.) seed and peel extract syrup against the growth of Escherichia coli. Papaya seed and peel extracts were formulated into syrup preparations with concentrations of 5% and 15%. Testing was carried out experimentally at the Microbiology Laboratory of the Yamasi Makassar Pharmacy Academy using the paper disk method on Nutrient Agar (NA) media, then incubated for 24 hours at 37°C. The measurement results showed that the inhibition zone in papaya seed extract syrup was 8.9 mm at a concentration of 5% and 10.28 mm at a concentration of 15%, which was categorized as moderate (6–10 mm). Meanwhile, papaya peel extract syrup produced an inhibition zone of 11.65 mm at a concentration of 5% and 13.45 mm at a concentration of 15%, classified as strong (11–20 mm). In conclusion, papaya seed and peel extract syrup with a concentration of 15% has a higher effectiveness in inhibiting the growth of Escherichia coli compared to a concentration of 5%.